GERMAN ORGANIZATIONAL CULTURE: AN EVALUATION IN TERMS OF HOFSTEDE’S CULTURAL DIMENSIONS, GERMAN STYLE MANAGEMENT, AND HUMAN RESOURCES MANAGEMENT (Third Sector Social Economic Review, 2020)
Germany is a major European country with a strong economy that stands out with its rigid management approach based on planning, efficiency, innovation, expertise and technical skills, World-famous brands and ‘Made in Germany’ quality. German culture is influenced by its historical background. In addition, because of the increasing need for labor after World War II, there is multiculturalism both in society and business life due to the recruitment of immigrant workers. In this context, how were the German business organizations and organizational culture shaped? In this review which aims to present an evaluation of the effects of national culture on organizational culture in the context of Germany’s historical background and its reflections in process of management, employment, and human resources management, explored that the national cultural dimensions influenced the German organizational culture. On the other hand, it has been determined that certain experiences in important historical periods had influence on culture, employment, management, and human resources management.
Keywords: German culture; German organizational culture; German style management; German business culture; German human resources management.